2010
DOI: 10.1002/cphc.201000365
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Lifetimes and Global Warming Potentials of CF3CH2CH2OH and CF3(CH2)2CH2OH

Abstract: A comprehensive study of several atmospheric degradation routes for two hydrofluoroalcohols, CF(3)(CH(2))(x=1,2)CH(2)OH, is presented. The gas-phase kinetics of their reactions with hydroxyl radicals (OH) and chlorine (Cl) atoms are investigated by absolute and relative techniques, respectively. The room-temperature rate coefficients (±σ, in cm(3) molecule(-1) s(-1)) k(OH) and k(Cl), are respectively (9.7±1.1)×10(-13) and (1.60±0.45)×10(-11) for CF(3)CH(2)CH(2)OH, and (2.62±0.32)×10(-12) and (8.71±0.24)×10(-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…However, in the coastal region where chlorine concentration increases, the atmospheric lifetime τClMBL decreases to 0.41 years. Similar observations have been made for other HFA molecules like CF 3 CH 2 CH 2 OH and CF 3 (CH 2 ) 2 CH 2 OH by Jiménez et al . Nevertheless, the very low atmospheric lifetime of this HFA molecule compared to CFCs ascertains that the molecule is very short‐lived and hence expected to have very low contribution to Global Warming Potential (GWP).…”
Section: Resultssupporting
confidence: 82%
“…However, in the coastal region where chlorine concentration increases, the atmospheric lifetime τClMBL decreases to 0.41 years. Similar observations have been made for other HFA molecules like CF 3 CH 2 CH 2 OH and CF 3 (CH 2 ) 2 CH 2 OH by Jiménez et al . Nevertheless, the very low atmospheric lifetime of this HFA molecule compared to CFCs ascertains that the molecule is very short‐lived and hence expected to have very low contribution to Global Warming Potential (GWP).…”
Section: Resultssupporting
confidence: 82%
“…[234] Previous experimental studies of 3,3,3-trifluoropropan-1-ol have reported values for RE in the range of 0.17-0.20 W m À2 ppb À1 (mean: 0.19 W m À2 ppb À1 ) [Jimenez et al, 2010;Sellevåg et al, 2007]. We have used absorption cross sections from Jimenez et al [2010], Sellevåg et al [2007] and Waterland et al [2005] and calculated the same RE of 0.02 W m À2 ppb À1 for all three spectra.…”
Section: Halogenated Alcohols and Ethersmentioning
confidence: 99%
“…[234] Previous experimental studies of 3,3,3-trifluoropropan-1-ol have reported values for RE in the range of 0.17-0.20 W m À2 ppb À1 (mean: 0.19 W m À2 ppb À1 ) [Jimenez et al, 2010;Sellevåg et al, 2007]. We have used absorption cross sections from Jimenez et al [2010], Sellevåg et al [2007] and Waterland et al [2005] and calculated the same RE of 0.02 W m À2 ppb À1 for all three spectra. Our calculated instantaneous REs of 0.21 W m À2 ppb À1 and 0.17 W m À2 ppb À1 using spectra from Jimenez et al [2010] and Sellevåg et al [2007], respectively, compare well with the previously published REs (which did not account for stratospheric temperature adjustment and lifetime correction).…”
Section: Halogenated Alcohols and Ethersmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, GWPs for short-lived compounds have been reported recently. [36][37][38][39] The plot of the cross-sections (cm 2 molecule -1 cm -1 ) as a function of wavenumber (cm -1 ) of the cis-3-hexene is shown in Figure 6. .…”
Section: Atmospheric Implicationsmentioning
confidence: 99%